The impact of body image on social cognition: Fear of negative evaluation mediates the relationship between body surveillance and interpersonal distance in women - Finn, Deanna; Cardini, Flavia; Aspell, Jane E.; Swami, Viren; Todd, Jennifer (Body image, 2024)
Interpersonal distance (IPD) refers to the distance naturally maintained during social interactions, while peripersonal space (PPS) refers to the immediate space surrounding the body, or the space within reaching distance. Previous research has preliminarily indicated that IPD is associated with body image disturbances. We sought to expand extant literature by exploring associations between aspects of positive and negative body image, IPD, and PPS. Seventy-five women from the United Kingdom aged 18–40 years completed measures of body appreciation, body image flexibility, body shame, body surveillance, and body dissatisfaction. IPD boundaries were estimated using a lab-based comfort-distance task, whereas PPS boundaries were estimated using an audio-tactile reaction-time task. Measures of body acceptance by others and fear of negative evaluation were completed as potential mediators. Overall, we identified positive associations between IPD, body surveillance, and fear of negative evaluation, with no statistically significant associations identified between the other indices. The association between active IPD and body surveillance was mediated by fear of negative evaluation, even after controlling for demographic factors. These findings suggest a nuanced relationship between IPD and body image-related factors, highlighting the role of social evaluation anxiety. Future investigations should use experimental designs to further understand these relationships and their implications. •Interpersonal distance (IPD) is the distance maintained during social interactions.•IPD was positively associated with body surveillance and fear of negative evaluation.•IPD was negatively associated with body acceptance by others.•Fear of negative evaluation mediated relationships between IPD and body surveillance.•Peripersonal space was not associated with positive or negative body image.